Modern machining technology: A practical guide - Davim J. P. Paulo (Woodhead Publishing in Mechanical Engineering)
Modern machining technology: A practical guide will provide practical information on modern machining technology for industry, with an emphasis on the processes used regularly across several major industries. Machining technology presents great interest for many important industries including automotive, aeronautics, aerospace, renewable energy, moulds and dies, biomedical, and many others. Machining processes are manufacturing processes in which parts are shaped by the removal of unwanted material; these processes cover several stages and are usually divided into the following categories: cutting (involving single point or multipoint cutting tools); abrasive processes (including grinding) and thermal advanced machining processes, namely LBM (laser-beam machining). This practical book can be used for teaching modern manufacturing technology, and will serve as a useful reference for manufacturing researchers, mechanical, manufacturing and industrial engineers, and professionals in related industries with machine-tools and manufacture experience. J. Paulo Davim is Aggregate Professor in the Department of Mechanical Engineering of the University of Aveiro and Head of MACTRIB - Machining and Tribology Research Group. He received his PhD in Mechanical Engineering from the University of Porto in 1997 and the Aggregation from the University of Coimbra in 2005. He has more than 25 years of teaching and research experience in machining, tribology and manufacturing processes. He is the Editor of several international journals, and also guest editor, editorial board member, reviewer and scientific advisor for many international journals and conferences. He has also published more than 300 articles in ISI journals (h-index 18 ) and conferences.